Cold Compress Using Ice Gel Effectively Reduces Pain Intensity in School Age Children (6-12 Years) During Infusion Procedures - Boediarsih Boediarsih; Adi Irawan; Dwi Kustriyanti (JENDELA NURSING JOURNAL, 2021)
Background: the infusion procedure is an invasive procedure that is often performed when treating children in the hospital, this action is done by inserting a needle into the child's vein which can cause pain. Cold compress using ice gel is one way to stimulate the skin so that it is therapeutic before infusion procedure.Purpose: to find out whether there is an effect of cold compresses using ice gel on the pain intensity during infusion procedure of school age children.Methods: this type of research is a quasi experiment two group posttest only design method. The population in this study were 32 children aged 6-12 years and the reaseach was taken at RSUD KRMT Wongsonegoro Semarang. The instruments were used ice gel compress, and were measured using pain intensity (OUCHER). The hypothesis test used the Wilcoxon test and Man-Whitney test.Results: data from 32 respondents obtained the results of the pain scale using the cold compress application. Ice gel against pain intensity of school-age children during infusion with p-value - 0,000 0.05. Thus, if p- 0.000 0.05 then Ho is accepted and Ha is rejected, which means that there is a significant difference in the pain scale between giving compresses (ice gel) to school-age children who are subjected to infusion.Conclusion: the application of cold compresses using ice gel can reduce the pain intensity of school-age children during the infusion procedure. That is recomended as the intervension during infusion procedure.